(untitled) (Plant Tissue Culture and Biotechnology, 2021)
In order to conserve diverse species of citrus, an experiment on in vitro micropropagation and production of synthetic seeds from in vitro regenerated plant propagules of the species; Citrus aurantifolia (Lime) was carried out in which shoot tips were found to be suitable for excapsulation of artificial seeds. Highest rate of germination was obtained from the shoot tips when MS was supplemented with 1 mg/l BAP. Beaded shoot tips produced maximum germination (81.43%). Germinated synthetic seeds with well established roots and shoots were were taken out from the culture bottles and transferred in plastic cups containing a mixture of sterile soil: sand and farmyard manure at a ratio of 1:1:1. Seedlings were further shifted in earthen pots and kept in a partial shed net house for 7 days. Those seedlings were finally transferred under the field conditions for acclimatization. Plant Tissue Cult. & Biotech. 31(1): 43-49, 2021 (June)